MENUMBUHKAN PENDIDIKAN KARAKTER ANTI KORUPSI MELALUI MODEL PEMBELAJARAN CARILEM - Intan Hestika Dhesi Ariani (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Anti-corruption character education is important in underlying the character ofchildren since early, in growing anti-corruption character in children need creative and innovative learning model so that what is expected from a learning activity can be reached maximally. CARILEM learning model in its implementation can not stand alone need the support of family and school synergies and relevant curriculum content. The purpose of learning is to grow the character of anticorruption through activities Reading, Storytelling and watch Educational filmsare packed attractively so that 9 values of anti-corruption character can beachieved optimally, children are able to show behavior changes to a betterdirection. This research uses Partisipatory Action Research (PAR) method andqualitative analyst approach so that it can answer the problem that happened atcertain time and area. The results showed that the CARILEM learning model iseffective in view of, 1) The achievement of indicators in accordance with the CoreCompetencies and Basic Competencies of the Curriculum. 2) Anti-corruptionbehavior is reflected in daily activities both at home and at school. 3) Terasahnyaability of the language of children well in reading the media story illustratedpicture book character of anti-corruption. 4) children are familiar with books andlove to read books that are good habits in shaping a behavior.Keywords: Growing, Character Education, Anti Corruption, Model Learning